Estimating multi-country VAR models - Fabio Canova; Matteo Ciccarelli (European Central Bank (ECB), 2006)
This paper describes a methodology to estimate the coefficients, to test specification hypotheses and to conduct policy exercises in multi-country VAR models with cross unit interdependencies, unit specific dynamics and time variations in the coefficients. The framework of analysis is Bayesian: a prior flexibly reduces the dimensionality of the model and puts structure on the time variations; MCMC methods are used to obtain posterior distributions; and marginal likelihoods to check the fit of various specifications. Impulse responses and conditional forecasts are obtained with the output of MCMC routine. The transmission of certain shocks across G7 countries is analyzed.
Keywords: C3; C5; E5; 330; Flexible priors; International transmission; Markov Chain Monte Carlo methods; Multi country VAR; VAR-Modell; International; Markov-Kette; Monte-Carlo-Simulation; Theorie; Schock; Konjunktur; G7-Staaten